Penerapan Teknologi Penyulingan Minyak Atsiri di Kosagrha Medayu - Renova Panjaitan; Susilowati; Djarwatiningsih; Sandy Buana Putra; Bambang Wahyudi; Mu’tasim Billah; Novel Karaman (Cv. Utility Project Solution, 2023)
Essential oil, especially citronella oil, is one of Indonesia's commodities with market opportunities that tend to increase. The increase in demand is due to its comprehensive utilization, such as in skin care products, perfumes, and even the energy sector started to employ it. This condition is undoubtedly an ample opportunity for Indonesia as the second contributor to citronella oil globally. This position needs to be maintained or increased by attracting people who have the potential to be involved in the essential oil sector. The Kosagrha Farmers Group is a community group in Medayu Selatan, Surabaya. Recently, that Group developed idle land in that area to become citronella cultivation. However, the problem was that these people were unfamiliar with the technology of processing citronella plants into essential oils. Therefore, the UPNVJT PKM Team organized a program for implementing essential oil distillation technology for the Farmer Group by going through several stages: socialization, practice, mentoring and evaluation. The technology transferred was distillation equipment with the principle of hydrodistillation. The results obtained from this program were that the members of the Farmer Group could understand the technique of extracting citronella essential oil and could operate the distillation technology equipment provided. Besides that, the community also expected other programs related to product downstream.